2022
DOI: 10.1177/03635465221131522
|View full text |Cite
|
Sign up to set email alerts
|

Survivorship and Reoperation of 324 Consecutive Isolated or Combined Arthroscopic Meniscal Allograft Transplants Using Soft Tissue Fixation

Abstract: Background: Meniscal allograft transplant (MAT) is an effective treatment for relieving symptoms and improving knee function in patients who experience symptomatic unicompartmental knee pain after a previous meniscectomy. However, the literature contains a paucity of studies assessing the survival rate and prognostic factors of soft tissue MAT. Purpose: To report the survivorship of a large, single-center cohort of consecutive patients treated with arthroscopic MAT using soft tissue technique and to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 34 publications
0
27
2
Order By: Relevance
“…56 Fourth, the Lysholm score was only collected at the final follow-up as a commonly used parameter for subjective outcome of MAT. 26,48,84 Therefore, it cannot be compared with a preoperative score. However, the KOOS and IKDC score were collected at 2 time points, and a correlation between scores has previously been reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…56 Fourth, the Lysholm score was only collected at the final follow-up as a commonly used parameter for subjective outcome of MAT. 26,48,84 Therefore, it cannot be compared with a preoperative score. However, the KOOS and IKDC score were collected at 2 time points, and a correlation between scores has previously been reported.…”
Section: Discussionmentioning
confidence: 99%
“…75,77 Furthermore, relevant information such as preoperative Kellgren-Lawrence or To ¨nnis grade, preoperative International Cartilage Regeneration & Joint Preservation Society (ICRS) grade, tibial slope, and leg alignment are often underreported, impeding interpretation of presented data. 11,26,37 Previous studies have identified generalized degenerative arthritis as a prognostic factor for poor allograft function and survival, leading to exclusion of these patients in a variety of studies. 26,48,55,63,73,79 However, recent evidence suggests that even in knees with severe focal chondral damage, MAT can be an effective treatment, leading to improved clinical scores and decreased pain, especially when combined with cartilage procedures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Meniscal allograft transplantation (MAT) is an established effective treatment for relieving pain in patients who underwent meniscectomy with a 10‐year survival rate ranging from 73 to 86% [6, 10, 19, 27, 29]. Despite such a high mid‐to‐long‐term survival rate, it occurs occasionally for early postoperative failure [7, 31].…”
Section: Introductionmentioning
confidence: 99%
“…Although no absolute definition of failure has been established, many studies have analyzed it based on clinical and surgical failures [8, 13, 20, 31]. Clinical failure is often defined as a Lysholm score of < 65 and surgical failure as the need for additional surgery after MAT [10, 23]. However, these parameters, while easy to measure, have limitations in offering an objective evaluation of the graft.…”
Section: Introductionmentioning
confidence: 99%